The Relationship Between Family Support And Medication Adherence Among Type II Diabetic Patients - Pakaya, Sri Wahyuni; Katili, Ansar; Basir, Ita Sulistiani (An Idea Health Journal, 2024)
Diabetes Mellitus is a chronic metabolic disorder characterized by high blood sugar levels. Consequently, this condition can cause various problems and complications, so patients’ medication adherence is essential to prevent complications. Apart from that, family support is also a factor that affects increasing medication adherence in type 2 DM patients. This research was classified as quantitative research using a descriptive correlation method with a Cross-sectional design. The research population was all type 2 DM patients with complications in the working area of Puskesmas (Public Health Center) Kabila, with as many as 516 people. In the meantime, the samples were 84 people determined through Accidental Sampling. The research findings indicated that 59 respondents (70.2%) had good family support, while 25 respondents (29.8%) had poor one. Meanwhile, 48 respondents (57.1%) adhered to taking medication, whereas 36 respondents (42.9%) did not.Additionally, the results of statistical tests using chi-square denoted a pvalue = 0.000 <?=0.05.In conclusion, there is a relationship between family support and medication adherence in type 2 diabetes Mellitus patients with complications in the working area of Puskesmas Kabila. Therefore, it is recommended that this research be used as reference material, and future researchers can develop research related to factors affecting medication adherence.